Circulating immune complexes in dogs with Leishmania infantum infection in a non-endemic country - Melanie Kaempfle; Katrin Hartmann; Yury Zablotski; Roswitha Dorsch; Nuria Parody; Jerónimo Carnés; Michèle Bergmann (PLoS ONE, 2026)
Circulating immune complexes (CIC) cause different organ lesions in canine leishmaniosis. This study aimed to measure CIC in dogs infected with Leishmania (L.) infantum in a non-endemic country and to analyze associations with disease parameters. Measurement of Leishmania -specific CIC was performed by a polyethylene glycol ELISA (cut-off: 0.274 optical density (OD)) every three months during a one-year study period in 52 L. infantum -infected dogs. Each appointment included a physical examination, complete blood count, serum biochemistry including C-reactive protein, urinalysis, L. infantum PCR and antibody ELISA. Statistical analyses included Mann-Whitney U tests, a multivariable robust linear regression, Spearman correlation, univariable logistic regression, and a receiver operating characteristic (ROC) curve. CIC levels differed significantly between dogs with and without lymphadenopathy ( p < 0.01; β =−0.38; 95% CI: −0.52, −0.24), uveitis ( p < 0.01; β=− 0.52; 95% CI: −0.89, −0.15), seborrhea/hypotrichosis ( p = 0.04; β =−0.11; 95% CI: −0.21, −0.01), and skin nodules ( p < 0.01; β = 0.22; 95% CI: 0.13, 0.31). Significant moderate to strong correlations with CIC levels were found for L. infantum antibodies ( p < 0.01; r s = 0.65; 95% CI: 0.57, 0.72), globulin ( p < 0.01; r s = 0.60; 95% CI: 0.51, 0.68), albumin-to-globulin ratio (p < 0.01; r s =−0.56; 95% CI: −0.65, −0.47) and total protein ( p < 0.01; r s = 0.46; 95% CI: 0.35, 0.56). CIC levels were significantly higher in dogs with positive lymph node PCR ( p = 0.04) as well as in dogs with disease relapses ( p < 0.01). The ROC curve analysis revealed one highly specific cut-off value at 1.668 OD for differentiating between dogs with and without disease relapse (98% specificity; 60% sensitivity). Measurement of Leishmania -specific CIC is useful for monitoring dogs with L. infantum infections and for indicating disease relapse.